Measuring the internal-market orientation in the public sector (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
The application of internal marketing in organizations has been researched by scholars for nearly three decades, but literature has little empirical research in the public sector. There is a latent debate on the relevance of internal marketing in the public sector, given the need to provide a more effective service to the citizens. Given the possibility that the internal-market orientation is an antecedent of job satisfaction, the objective of this research was to measure the level of internal market orientation in the public sector, and the Military Fire Department of the State of Espírito Santo (MFDESS) was surveyed using quantitative research. The instrument for data collection was a structured questionnaire, which follows the model used by Gounaris (2006) in research with employees of a hotel chain in Greece. 522 firefighters were surveyed. The choice of this organization was due to the importance of the service performed and the society visibility, given the direct relationship with life and assets of the taxpayers. Therefore, the level of job satisfaction of firefighters is relevant for the achievement of excellence in their missions. The results showed that firefighters have the perception that there is little internal-market orientation in the Military Fire Department and the level of job satisfaction is low.  The research result converged with the literature on the direct relationship of the internal-market orientation with job satisfaction.  Furthermore, the research concluded that job satisfaction is influenced by the identification of the exchange of value, segment internal market, job description, management concern and training.Keywords: internal marketing, public sector, internal-market orientation, job satisfaction.